Developing minority language resources : the case of Spanish in California - Valdés, Guadalupe (Bilingual education and bilingualism., 2006)
This book documents ongoing language shift to English among by Latino professionals in California. It then describes current instructional practices used in the teaching of Spanish as an academic subject at the high school and university levels to "heritage" language students who, although educated entirely in English, acquired Spanish at home as a first language. It specifically examines the potential contribution of these instructional practices to the maintenance of Spanish.